Daily activity and diet of Talaud bear cuscus (Ailurops melanotis Thomas, 1898) on Salibabu Island, North Sulawesi, Indonesia - Terri Repi; Burhanuddin Masyud; Abdul Haris Mustari; Lilik Budi Prasetyo (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Authors. 2019. Daily activity and diet of Talaud bear cuscus (Ailurops melanotis Thomas, 1898) on Salibabu Island, North Sulawesi, Indonesia. Biodiversitas 20: 2636-2644. Talaud bear cuscus (Ailurops melanotis) is an endemic species in the Sangihe and Talaud Islands, North Sulawesi, Indonesia. This species is critically endangered in the IUCN Redlist, with a declining population trend. As a protected species in Indonesia, there has not been any specific research on this species. This research aimed to determine the daily activity pattern of talaud bear cuscus based on sex and age classes, and provide the first preliminary data on its dietary diversity and preference. Data collection was conducted on Salibabu Island (Talaud Islands District, North Sulawesi, Indonesia) for approximately three months (May-July 2016). The talaud bear cuscus spent most of its time resting 78.19%, moving 14.98%, feeding 3.49%, grooming 3.06%, and social 0.28%. Talaud bear cuscus fed on 22 species in its daily diet consisting of 20 tree species and 2 liana species. Cuscus fed mainly on young leaves (57.48%) followed by petioles (leaf stalk) (17.60%), mature leaves (15.33%), bud (7.19%), flowers (1.32%) and unripe fruit (1.07%). This preliminary data about the behavior, activity patterns, and diet of talaud bear cuscus, in general, can be used as supporting information in cuscus conservation efforts, especially habitat management related to the availability of feed resources and to determine the time of the survey and to understand the general behavior and ecology of this species.